2016
DOI: 10.1016/j.cgh.2016.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Absolute Denial of Modern Hepatitis C Therapy by Type of Insurance

Abstract: Background & Aims The high costs of direct-acting antiviral (DAA) agents to treat chronic hepatitis C virus (HCV) infection have resulted in denials of treatment, but it is not clear whether patients’ access to these therapies differs with their type of insurance. Methods We conducted a prospective cohort study among all patients who had a DAA prescription submitted between November 1, 2014 and April 30, 2015 to Burman’s Specialty Pharmacy, which provides HCV pharmacy services to patients in Delaware, Maryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 36 publications
7
86
2
Order By: Relevance
“…43 It also adds to the stress and distress experienced by patients who are waiting to receive treatment. These restrictive policies, however, are contrary to the recommendations of professional medical societies.…”
Section: Viral Hepatitis Stigma and Discriminationmentioning
confidence: 99%
“…43 It also adds to the stress and distress experienced by patients who are waiting to receive treatment. These restrictive policies, however, are contrary to the recommendations of professional medical societies.…”
Section: Viral Hepatitis Stigma and Discriminationmentioning
confidence: 99%
“…Analysis of a large French HIV cohort between 2000–12 indicated that 5,562 of 34,308 had HCV infection, but that HCV prevalence had decreased and treatment initiation increased with availability of DAAs, suggesting that HCV prevalence will continue to decline in coming years [89]. A prospective cohort from one specialty pharmacy serving patients in Delaware, Maryland, New Jersey, and Pennsylvania between November 2014 and April 2015 found significant disparities in DAA access based on insurance, with nearly half of Medicaid patients having declined applications [90]. Much effort will continue to be appropriately focused on the question of DAA access and affordability.…”
Section: Diagnosis Cost and Accessmentioning
confidence: 99%
“…In contrast, several effective direct-acting antiviral drugs (DAAs) targeting HCV viral factors efficiently block HCV replication and result in a sustained virological response (viral cure) in over 90 percent of patients [52, 53]. However, due to the high cost of DAA treatment and the lack of a HCV vaccine, HCV eradication is going to be challenging and elusive particularly in the developing world [54, 55]. …”
Section: Ips-derived Hepatocyte-like Cells As Models To Study Infectimentioning
confidence: 99%